Mapping the Information Services of NAAC Accredited Government Aided General Degree College Libraries in Bankura: An Investigation. (LIS TODAY, 2025)
The library assumes an extremely indispensable part in the advanced education  framework by giving pertinent data and information to the academic local area and is  treated as the core of the scholarly framework. The changing in the data climate, and the  use of the ICT framework in libraries have made both library experts and users befuddled  to find suitable data as and when required. The investigation of the utilization of library  services and users’ fulfillment extraordinarily affects future library administrations by  updating the library assortment advancement strategy and administrations in view of  users’ perspectives and requests and for this assessment of user fulfillment with library  assets and administration is important to give information sources and services to meet  user’s data prerequisites however no review is being done work today to know the  utilization of library assets and client fulfillment on libraries’ resources and services in  NAAC Accredited, Government Aided General Degree College Libraries in Bankura.
Keywords: Academic Library; Information Source; Information Service; Users